2021
DOI: 10.1111/vde.13003
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver reliability of Feline Dermatitis Extent and Severity Index (FEDESI) and Scoring Feline Allergic Dermatitis (SCORFAD) and the relationship between lesion scores and pruritus

Abstract: Background Feline Dermatitis Extent and Severity Index (FEDESI) and Scoring Feline Allergic Dermatitis (SCORFAD) are scales used to assess lesion severity in cats with allergic dermatitis. Interobserver reliability has not been assessed for either. Hypothesis and objectives To determine interobserver reliability for FEDESI and SCORFAD, and the relationship between lesion scores and pruritus. Animals Thirty‐eight cats presenting for pruritus. Methods and materials Each cat’s lesions were scored by two observers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Recently, two studies evaluated the correlation between Feline Dermatitis Extent and Severity Index (FEDESI) and Scoring Feline Allergic Dermatitis (SCORFAD) and also assessed the correlation between these scoring systems and a pruritus VAS scale designed for dogs, with contradictory results. 38,39 The same studies repeated using the VAScat should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two studies evaluated the correlation between Feline Dermatitis Extent and Severity Index (FEDESI) and Scoring Feline Allergic Dermatitis (SCORFAD) and also assessed the correlation between these scoring systems and a pruritus VAS scale designed for dogs, with contradictory results. 38,39 The same studies repeated using the VAScat should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Although IDT is occasionally used as a second‐line diagnostic to confirm negative SPT results in people, the clinical significance of these confirmatory positives is questionable 4 . A recently completed study by the authors, which utilised SPT for testing cats, showed that this technique allowed for very rapid testing (1/8th the time needed for IDT) and could usually be conducted without sedation 5 . These advantages make SPT a very attractive option for the allergen testing of atopic pets.…”
Section: Introductionmentioning
confidence: 99%